2006
DOI: 10.1093/nass/nrl153
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of DNase I activity

Abstract: DNase I in one microl of the water could quantitate electrochemically with the detection limit of 0.01 units (ca. 20 pg) by using the ferrocenyl oligonucleotide-immobilized electrode prepared by thiolated oligonucleotide and ferrocenyl carbodiimide as a simple labeling reagent of redox unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This behavior is similar to previous work, where electrochemically active DNA ligand showed a lower slope than that after hybridization with the complementary DNA. 15 The ligand was more concentrated to the doublestranded DNA than to the single-stranded DNA on the electrode. This also showed that 1 could be used for estimating the amount of mRNA on the electrode, and could detect a decreasing amount of mRNA on the electrode after digestion with RNase.…”
Section: Treatment Of Mrna-immobilized Electrode With Rnase Amentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is similar to previous work, where electrochemically active DNA ligand showed a lower slope than that after hybridization with the complementary DNA. 15 The ligand was more concentrated to the doublestranded DNA than to the single-stranded DNA on the electrode. This also showed that 1 could be used for estimating the amount of mRNA on the electrode, and could detect a decreasing amount of mRNA on the electrode after digestion with RNase.…”
Section: Treatment Of Mrna-immobilized Electrode With Rnase Amentioning
confidence: 99%
“…[7][8][9] Electrochemistry is generally expected to achieve high-sensitive analysis with an inexpensive, compact instrument; this technique has been applied to DNA detection. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Electrochemical DNA analysis so far reported is briefly grouped into two methods based on the ways to be used for electrochemically active labeling of DNA [10][11][12][13][14][15] and an electrochemically active DNA indicator. [7][8][9][16][17][18][19][20][21] Highly sensitive DNA detection was achieved in both methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA or RNA cleavage reactions catalyzed by nucleases such as restriction nucleases and nonspecific nucleases are essential in a variety of fields ranging from biotechnology to pharmacology, as well as in biological processes involving replication, recombination, DNA repair, molecular cloning, genotyping, and mapping. Recent attempts to attach restriction endonucleases to nanostructures have been undertaken due to the well-established ability of the endonucleases to cleave DNA at specific recognition sites. Traditional techniques, including gel electrophoresis, high-performance liquid chromatography (HPLC), electrochemical study, and enzyme-linked immunosorbent assay (ELISA) have been established in assaying nuclease activities. These protocols share the drawbacks of being time-intensive, DNA-consuming, discontinuous, laborious, and usually requiring isotope labeling. Many of these limitations are now being addressed by the development of fluorescence assays based on fluorescence quenching or fluorescence resonance energy transfer (FRET). Although promising, these techniques are compromised by the requirement for double-labeled DNA probes, limited chemical stability, and interferences by external nonspecific events.…”
Section: Introductionmentioning
confidence: 99%